ZCT 106/4- Electronic - PPSF, Pusat Pengajian Sains Fizik (Universiti Sains Malaysia, 2001)
UNIVERSITI SAINS MALAYSIA Second Semester Examination 2000/2001 Academic Session February/Marc 2001 ZCT 106/4- Electronic Time : 3 jam Please check that the examination paper consists of FOURTEEN printed pages before you commence this examination. Answer all FOUR questions. Candidates may choose to answer all questions in the Malay Language. If candidates choose to answer in the English Language, it is compulsory to answer at least one question in the Malay Language.